INFLUENŢA STEREOTIPURILOR ÎN VIAŢA SOCIALĂ - USM ADMIN (Moldova State University, 2011)
Stereotypes play a fundamental role in our lives, causing directly or indirectly, more or less visible, our behaviors. The concept of "stereotype" was first used by Lippmann, as representing a set of images" that are indispensable in order to cope with information sent from our environment." The most popular metaphor of Lippmann on the stereotype is that of "images in our minds." In his view, human beings do not respond directly to external reality, but to a representation of the environment which is more or less created by the individual himself. A definition accepted by most authors would be presenting stereotypes as "a shared set of beliefs regarding the personal characteristics of personality traits and behavior that are specific to a group of people".